What are The Rates of Mortality, Major Morbidity, and Hospital Readmission Within 30 Days Following Elective Gynecological Procedures in Patients Over 80 Years? : A Systematic Review - Melati Ganeza; Yahya Nurlianto; Mutia Juliana (The International Journal of Medical Science and Health Research, 2026)
Introduction: The global population is aging, and more women over 80 years are considered for elective gynecological surgery. However, evidence on short-term postoperative outcomes in this specific age group remains scarce. Methods: We conducted a systematic review following PRISMA guidelines, searching multiple databases for studies reporting 30-day mortality, major morbidity, or hospital readmission after elective gynecological procedures in patients ≥80 years. Observational studies, RCTs, etc were included. Results: The pooled 30-day mortality was 0–1% (Friedman et al., 2006; Fitzgerald et al., 2008). Major morbidity was elevated in elderly patients, particularly medical complications (UTI, respiratory failure, sepsis) (Friedman et al., 2006; Bourgin et al., 2016). No study reported 30-day readmission rates specifically for patients over 80. Length of stay was consistently longer in older patients (Friedman et al., 2006; Gultekin et al., 2015). Minimally invasive and obliterative procedures (e.g., colpocleisis) were associated with better outcomes (Raffone et al., 2021; Sadeh et al., 2022). Discussion: There is a profound evidence gap regarding perioperative outcomes in women over 80 undergoing elective gynecological surgery. Available data suggest low mortality but increased morbidity compared to younger patients. Readmission remains unmeasured. Frailty, hypoalbuminemia, and open surgical approach are key risk factors. Conclusion: Elective gynecological surgery in selected patients over 80 is feasible with low mortality, but major morbidity is higher. No readmission data exist. Future research must include this age group, report geriatric-specific outcomes, and evaluate ERAS protocols.